Novel Biomarkers of SLE with Renal and Neuropsychiatry Complications - Nawaz, Mariam; Nazir, Haseena; Arshad, Tooba; Sohaib, Muhammad; Iqbal, Waseem; Jalil, Fazal (Indus Journal of Bioscience Research, 2025)
SLE is a complex multi-organ autoimmune disease exhibiting renal, dermatological, neuropsychiatric, and cardiovascular symptoms. In this autoantibodies attack their own organs and immune complex formation occurs as well and ultimately leads to death. Its causes are relatively unknown but complex environmental, genetic, hormonal, and immunological factors are involved in it. This review article summarizes the insights of the past 5 years of research about biomarkers, including activity, monitoring, prognosis, diagnosis, genetic, complement, and traditional biomarkers of SLE with Lupus and neuropsychiatric complications. Our initial search for articles was based on a search from NCBI and PubMed, along with journals from Frontier, Nature Science, and PNAS. Novel Biomarkers in SLE that showed complication with LN and NPSLE are IL-6, IL-16, IL-10, IL-18, IL-1ra, and IL-1b, (cytokine biomarker), Osteopontin (serum biomarker), Lipocalin-2 (NGAL), M-CSF (CSF-1, and M-CSF), Anti-ribosomal P+, VCAM-1, TNF-a, Serum Uric Acid (SUA), Ceruloplasmin, C3 complement components were involved both in NPSLE and LN disease activity of the patients. Also, biomarkers like Angiostatin have shown excellent sensitivity (88%) but poorer specificity (44%) with an AUC value of 0.65 in NPSLE while NLR and PLR showed high sensitivity (90%, 95%) and specificity of (50%, 50%) in LN. We opted for tools that can diagnose, assess disease activity, and predict flares more accurately without conducting an unhealthy process like Biopsy. So this review article is focused on finding the Biomarkers from Blood, Urine, and CSF, with diagnosis, prognosis, and predictive value (Though not clinically validated). It also discusses its use in developing Diagnostics and disease monitoring panels which could further improve SLE diagnosis and assessment of D.A. thus improving the overall patient’s condition. However, more thorough research is required due to the general absence of confirmation research among different groups.